(untitled) (Società e diritti, 2023)
With sentence no. 72 of 2022, the Constitutional Court faces an interesting question dedicated to the purchase of ambulances in reference to a tax relief contained in the Third Sector Code; the decision is characterized by the fact that, after having declared unfounded the question of constitutional legitimacy in relation to the principle of reasonableness, the Court urges the legislator to modify the current provision because it unreasonably excludes other subjects from the benefit.